Students' Attitudes Towards Women in Science and Technology (R&E-SOURCE, 2025)
Students' attitudes toward women in science and technology reveal persistent gender disparities, shaped by cultural biases, educational experiences, and perceptions of belonging. This study investigates these attitudes, focusing on differences between students in the fields of science and technology and those in the humanities. The research explores three main objectives: comparing attitudes across disciplines, analysing gender differences in perceptions, and examining variations between undergraduate and graduate students. Despite global efforts to address gender disparities in science and technology through scholarships, mentorship programs, and diversity policies, women remain underrepresented, comprising only 33% of researchers worldwide, with notable gaps in engineering, physics, and computer science. These disparities highlight the importance of understanding student perceptions, as such attitudes influence both women’s participation in STEM (Science, Technology, Engineering and Mathematics) and societal views on gender roles in science and technology. Findings from this study provide insights into the extent to which academic disciplines and educational levels shape attitudes toward women in STEM.